1993
DOI: 10.1111/j.1532-5415.1993.tb07456.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Plasma IGF‐I in Poliomyelitis Survivors

Abstract: Lower levels of IGF-I are seen in polio survivors, and this finding correlates with ADL dysfunction. The hyposomatomedinemic tendency of polio survivors may have an adverse effect on their neuromuscular function and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…A possible explanation is that spasticity maintained the IGF-1 profile despite lower GH. This observation is confirmed by another finding that clearly documented that persons with poliomyelitis have diminished IGF-1 profiles [20]. Persons with poliomyelitis commonly experience flaccid paralysis due to injury of their alpha motor neurons.…”
Section: Discussionsupporting
confidence: 61%
“…A possible explanation is that spasticity maintained the IGF-1 profile despite lower GH. This observation is confirmed by another finding that clearly documented that persons with poliomyelitis have diminished IGF-1 profiles [20]. Persons with poliomyelitis commonly experience flaccid paralysis due to injury of their alpha motor neurons.…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, mean levels of IGF-1 in patients were not abnormal and there was no significant correlation between IGF-1 levels and maximal 31,33 A recent study reports a negative correlation between muscle force and IGF-1 levels. 38 Serum creatine kinase levels were mildly increased in prior-polio patients.…”
Section: Discussioncontrasting
confidence: 60%
“…It remains to be determined whether decreased levels of IGF-1 are linked to impairment in voluntary activation in these patients and whether the maximal level of voluntary activation improves when IGF-1 levels are increased. 31,33,35,38 Some investigators 40,42 have found increased serum creatine kinase levels in postpolio patients. Therefore, we hypothesized that IGF-1 and creatine kinase may predict impaired voluntary activation and impaired endurance, respectively.…”
mentioning
confidence: 97%
“…In a pilot study of 10 PPS patients Shetty KR et al [17] reported the mean serum [IGF-I] to be approximately 50% lower than age matched controls. A larger study by Rao et al [18] of 124 PPS patients and 261 age matched controls also reported a 25% lower mean [IGF-I] in the PPS patients. The authors considered this to be indicative of an overall reduction in peripheral IGF bioactivity.…”
Section: Discussionmentioning
confidence: 82%
“…The absence of detailed information on the endogenous peripheral IGF system in disease states may be one of the limitations in the design of these clinical trials. To date, conflicting studies of the circulating IGFs report normal or decreased levels of IGF-I in ALS [13][14][15] and post polio syndrome (PPS) [16][17][18] but unchanged levels of IGF-I in MS [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 98%